Implementation of Maqasid al-Syari’ah in Islamic Banking: Historical Analysis, Urgency, and Review of Al-Daruriyyat Al-Khams Indicators - Emi Sri Rahayu Fatimah; Andi Muh. Taqiyuddin BN; Yusril Mahendra; Zulfajrin (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Maqasid al-Syari'ah is a fundamental pillar of Islamic law, oriented towards achieving human welfare, particularly in the economic sphere. This approach plays a strategic role as a philosophical foundation for the practice, product development, and the system of Islamic banking, enabling them to respond ethically to contemporary business dynamics. This study aims to examine in depth the definition, urgency, classification, and historical trajectory of Maqasid al-Syari'ah, and to analyze its implementation in the current Islamic banking industry. The method used is library research, in which data are collected from primary and secondary sources and analyzed descriptively and analytically. The results of the study indicate that the evolution of Maqasid al-Syari'ah thought transcends the historical phases of pre-codification and codification. This study confirms that the implementation of Maqasid al-Syari’ah in Islamic banking is not merely the fulfillment of formal legal aspects, but rather the embodiment of five main indicators (al-daruriyyat al-khams), namely the protection of religion (al-din), soul (al-nafs), reason (al-’aql), descendants (al-nasl), and property (al-mal). By integrating these values, Islamic banking is expected to mitigate negative practices such as usury, fraud, and corruption, thereby realizing substantive economic justice. The implication is that strengthening the understanding of Maqasid al-Syari’ah is crucial for stakeholders to maintain the integrity, business morality, and competitiveness of Islamic banking amidst rapid global progress.